Disruptive conduct: the impact of disruptive technologies on social relations in higher education. Issue 1 (2nd January 2016) - Flavin, Michael
Abstract : Higher education institutions (HEIs) have invested significantly in digital technologies for learning and teaching. However, technologies provided by HEIs have not been universally successful in terms of adoption and usage. Meanwhile, both students and lecturers use disruptive technologies to support learning and teaching. This article examines the impact of disruptive technologies in higher education, using activity theory as a lens through which to consider their impact. Data are gathered from a questionnaire and interviews. The research suggests that participants provide explanation for disruptive technologies from their experience in handling them, rather than in keeping with a designer's intentions, and therefore, the participants/users prefer convenient and easy-to-use technologies . The application of disruptive technologies has implications for how knowledge is accessed, for the division of labour in higher education and for the role of the HEI as gatekeeper to knowledge.